ANALISA PENGENDALIAN INTERN SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN OUTSOURCING PADA PT SWABINA GATRA - Yanti, Indah Dwi; Reviandani, Wasti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the implementation of internal control of the outsourced employee payroll accounting information system and what are the constraints of the internal control of the outsourced employee payroll accounting information system. The data used in this study were obtained from interviews, literature studies, and documentation. The method used in this study is a qualitative descriptive method using data reduction analysis techniques, data presentation, and data inference. The result of this research is that the implementation of internal control of the accounting information system is in accordance with the provisions of the company. Starting from a clear segregation of duties, internal control environment, required supporting documents, accounting procedures, to payment terms. The obstacle experienced by the company was that there had been a discrepancy between the salaries received by outsourced employees and evidence of attendance records in the system caused by errors in the attendance application system.